ETHICS: MAlN CLASIFICATIONS - Polo Santillan, Miguel (2007)
Severa! doctrines and ethical theories trying to understand human action make the historyof Ethics. To classify them will allow us to offer a clear understanding of a myriadof filosophical schools and tendencies trying to help us in solving ethic problems. Thisclassification confronts contending theories thus leading the readers to a better evaluationof their arguments.